Pada minimarket, produk merupakan bahan pokok yang akan dijual belikan. Produk di minimarket ini akan menentukan pengelompokkan data stok barang di Toko Toba. Dengan adanya masalah ini, perlu untuk menciptakan sistem baru menggunakan Rapidminer yang dapat - Fauziah, Irfa Mulhimah; Amalia, Dita Rizki; Wahyudin, Edi; Mulyawan, Mulyawan; Kaslani, Kaslani (LPPM UNIKA Santo Thomas Medan, 2022)
In minimarkets, the product is a staple that will be sold and bought. The products in this minimarket will determine the grouping of stock data at the Toba Store. Given this problem, it is necessary to create a new system using Rapidminer that can group stock data at Toko Toba, which was carried out at the Toko Toba Sedong minimarket and carried out in November 2021-January 2022. This k-means algorithm will not be affected by the order of objects which has been used. In stock management that is carried out inaccurately and carelessly will cause very high and uneconomical storage costs, because there can be vacancies or excess goods and certain types of items. This study aims to group stock data using Rapidminer at Toba Stores into 2 clusters. The method that will be used in this research is using the K-Means Clustering method. This research is also strongly supported by 1 data mining tool, namely Rapidminer. Data mining on Rapidminer tools for cluster 0 there are 15 items and the data contained in it, for cluster 1 there are 9 data contained in it.